Loganin Inhibits Angiotensin II–Induced Cardiac Hypertrophy Through the JAK2/STAT3 and NF-κB Signaling Pathways - Xu, Jia-jia; Li, Run-jing; Zhang, Zheng-hao; Yang, Cui; Liu, Shi-xiao; Li, Yan-ling; Chen, Min-wei; Wang, Wei-wei; Zhang, Gong-ye; Song, Gang; Huang, Zheng-rong (Frontiers in Pharmacology, 2021)
Loganin is an iridoid glycoside extracted from Cornus officinalis, which is a traditional oriental medicine, and many biological properties of loganin have been reported. Nevertheless, it is not clear whether loganin has a therapeutic effect in cardiovascular diseases. Hence, the aim of the present study was to investigate the effect of loganin on Ang II-induced cardiac hypertrophy. In the present study, we reported for the first time that loganin inhibits Ang II- provoked cardiac hypertrophy and cardiac damages in H9C2 cells and in mice. Furthermore, loganin can achieve cardioprotective effects through attenuating cardiac fibrosis, decreasing pro-inflammatory cytokine secretion, and suppressing the phosphorylation of critical proteins such as JAK2, STAT3, p65 and IkBa. Besides, the outstanding findings of the present study were to prove that loganin has no significant toxicity or side effects on normal cells and organs. Based on these results, we conclude that loganin mitigates Ang II-induced cardiac hypertrophy at least partially through inhibiting the JAK2/STAT3 and NF-kB signaling pathways. Accordingly, the natural product, loganin might be a novel effective agent for the treatment of cardiac hypertrophy and heart failure.